Role of Intestinal Microflora on Necrotizing Enterocolitis in Preterm Infants - Wu, Lijuan; Lin, Hung-Chih (Journal of Pediatric Biochemistry, 2015)
Necrotizing enterocolitis (NEC) remains a devastating intestinal disease in preterm very low-birth-weight (VLBW: <1,500 g) infants. Though the pathogenesis of NEC in preterm VLBW infants is not fully explored, numerous clinical evidence and laboratory data have supported that the bacterial colonization is a critical factor for NEC development. Recent evidence has suggested that NEC is associated with both unusual intestinal microbial species and an overall reduction in the diversity of microbiota. Nonetheless, preterm infants have very unique microflora colonization in the intestinal tract because many preterm infants are born via cesarean section and are mandated to develop intestinal microflora colorization within the complex neonatal intensive care unit. Furthermore, preterm infants show delayed colonization by “healthy commensal” organisms, especially bifidobacteria and lactobacilli. All these data suggest that low colonization of Bifidobacterium and Lactobacillus in preterm VLBW infants may serve as a predisposing factor in microbial infection and NEC. Based on these findings, researchers have tried to use probiotics to prevent NEC in prematurity; there are 27 randomized controlled trials and 7 recent meta-analyses which enrolled a total of 6,655 preterm infants. All the evidence confirmed that oral probiotics effectively prevent NEC and death in preterm infants. Premature rat model and updated meta-analysis further showed that combined probiotics strains resulted in a marked reduction of the incidence of NEC. Future study should focus on the head-to-head control trial on different probiotics regimen and possible use of the microbiome of breast-fed preterm infants for total fecal transplantation to eradicate NEC.
Keywords: intestinal microflora; necrotizing enterocolitis; preterm infants